ECOLOGY IN MACEDONIAN LITERATURE FOR CHILDREN: CULTURAL IMPLICATIONS FOR SOCIAL CHANGES - Jasmina Mojiseva-Gusheva (Philological Studies, 2022)
Literature can be one of the important factors in raising environmental awareness and educating the youth. The paper starts with the assumption that reading fiction with environmental content encourages care for the environment, emphasizes the need for proper management of natural resources, develops a love for nature and every living being, as well as implies awareness of ecosystem preservation. Through an appropriate analysis of Macedonian children's literary works that deal with environmental topics (eco-awareness, eco-education, pollution, natural environment, protection of animal species, eco-activism) we come to certain conclusions about the quality, shortcomings, and the state of eco-awareness among the children's population in Macedonia. More specifically, the paper will analyze children's science fiction novels: "Planet Octaltz" (1988) by Liliana Beleva (dedicated to an ecological cataclysm); "The Adventures of Marko and Damjan" (2005) by Mirko Zafirovski (who initiates the search for an unpolluted planet). Then, we shall focus on the youth novel "Poplars at the End of Grandfather's Meadow" (2001) by Bistrica Mirkulovska (as an illustration of school ecoactivism); the children's novel "Kinder Kvacka" (1999) by Kiro Donev (through which children can properly and unobtrusively learn about environmental content from an early age); the novel "Professor Ednokamchev" (1999) by environmental activist Mimosa Ristova (dedicated to the problem of the survival of wild bears) and finally the eco-novel "Green Story" (2008) by Zvonko Sharevski (which deals with the problem of forced reclamation).The performed analysis revealed the problems of insufficient representation of children's environmental literature in formal education, use of literary forms not adapted to the age of children, as well as inadequately processed contents.This paper aims at discovering how the analyzed literary works reflect the relationship of man to the environment in which he lives, highlighting the importance of environmental topics for humanity. All of this is done with one basic goal to initiate the need to create adequate eco-literature in Macedonia, which will lead to changes in the overall attitude of society towards nature.